RISK FACTORS FOR INEFFECTIVE CHEMOTHERAPY IN PATIENTS WITH MULTIDRUG-RESISTANT TUBERCULOSIS - O. V. Filinyuk; I. G. Felker; G. V. Yanova; L. N. Buinova; O. V. Kolokolova (Туберкулез и болезни лёгких)
The social, clinical, radiological, and bacteriological causes of DOTS-PLUS failure were analyzed. According to the findings, diagnosis at the early stage of fibrocavernous tuberculosis, respiratory failure, or hemoptysis in the presence of chronic bronchitis, gastrointestinal and urinary tract diseases, as well as in prison increased the risk of poor therapy outcome. Massive bacterial excretion, high rate of secondary resistance development in Mycobacterium tuberculosis, and its drug resistance to five agents or more are maximally associated with treatment failure in patients with multidrug-resistant tuberculosis.